Gastric Metastasis from Hepatocellular Carcinoma: A Rare Manifestation - Abdul Hakim, Mohamed Seenikatty; Azmi, Ahmad Najib; Jayalakshmi, Pailoor; Mahadeva, Sanjiv (Springer, 2018)
[No abstract available]